Investigation of the antimicrobial activities of various antimicrobial agents on Streptococcus Mutans Sortase A through computer-aided drug design (CADD) approaches. (November 2021) - Salmanli, Merve; Tatar Yilmaz, Gizem; Tuzuner, Tamer
Highlights: SrtA, is a potential target in the development of antimicrobial and caries prevention agents. For the first time, 178 compounds were examined against S.mutans SrtA at the molecular level with CADD methods. 6 compounds showed better binding affinity towards SrtA than the positive control compound (CHX). This study provides guidance for future clinical research by testing of many chemical compounds for the treatment of caries in a more reliable, cost-effective and time-saving manner. Abstract: Background and objective: Tooth decay is a common chronic disease that causes pain, tooth loss, malnutrition, anxiety and significantly affects half of the world's population. Streptococcus mutans (S.mutans), is considered the main pathogen causing tooth decay. Sortase A (SrtA), one of the surface proteins of S. mutans, is a potential target in the development of antimicrobial and caries prevention agents for preventing infections associated with biofilm formation. Recently, various SrtA inhibitors, including small molecules and natural product, especially, trans-chalcone, chlorhexidine (CHX) and flavonoid compounds, which exhibit effective inhibition against SrtA, have been identified. However, due to the limited number of inhibitors, multi-drug resistance and side-effects the discovery of new inhibitors for SrtA is essential. Methods: In this case, various compounds aimed at the target enzyme underwent high-throughput screening with small molecule libraries. For this screening of a total of 178 compounds, 163 were found to be pharmacokinetically suitable by performing an absorption, distribution, metabolism, and excretion (ADME) analysis. Molecular docking was then applied to investigate the interaction mechanism among these suitable compounds and the target enzyme structure at the molecular level. Results: According to the results of the study, six compounds (CHEMBL243796 (kurarinone), CHEMBL2180472, CHEMBL3335591, CHEMBL373249, CHEMBL1395334, CHEMBL253467 (Isobavachalcone)) exhibited lower docking scores (–7.18, –6.59, –6.53, –6.47, –6.43, and –6.39 kcal/mol, respectively) against S. mutans SrtA than the positive control CHX (–6.29 kcal/mol). Finally, the 100 ns molecular dynamic simulations and binding free energy calculations were performed for the structure stability analysis of the enzyme with CHEMBL243796 (kurarinone), which showed the lowest docking score. As a result of these studies, the stability of the critical interactions between kurarinone and the target enzyme was preserved during the simulation time. Conclusions: These results indicate that flavonoid and chalcone scaffold compounds are clinically more reliable and potent than CHX as novel inhibitory agents for inhibiting oral biofilm formation. These finding can provide important contribution to the future clinical trials in the development of therapeutically useful inhibitors of SrtA by virtually screening several chemical compounds more rapidly to select suitable compounds for the prevention and treatment of dental caries.